2021
DOI: 10.3390/healthcare9121684
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles and Solutions Driving the Development of a National Teleradiology Network

Abstract: Background: Teleradiology has the potential to link medical experts and specialties despite geographical separation. In a project report about hospital-based teleradiology, the significance of technical and human factors during the implementation and growth of a teleradiology network are explored. Evaluation: The article identifies major obstacles during the implementation and growth of the teleradiology network of the Berlin Trauma Hospital (BG Unfallkrankenhaus Berlin) between 2004 and 2020 in semi-structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
(46 reference statements)
1
4
0
5
Order By: Relevance
“…This may lead to questions on whether those radiologists would prefer in-house reporting rather than interpreting images off-site, or whether they may not yet be familiar with teleradiology systems or have used teleradiology in their clinical practice and thus could not express real opinions on their experiences. This result was consistent with the results of the study carried out by Goelz et al 22 (2021), who found that some radiologists have concerns related to the speed of communication, the equality of reports, residents’ training, the instability of the job market, and radiologists’ incomes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may lead to questions on whether those radiologists would prefer in-house reporting rather than interpreting images off-site, or whether they may not yet be familiar with teleradiology systems or have used teleradiology in their clinical practice and thus could not express real opinions on their experiences. This result was consistent with the results of the study carried out by Goelz et al 22 (2021), who found that some radiologists have concerns related to the speed of communication, the equality of reports, residents’ training, the instability of the job market, and radiologists’ incomes.…”
Section: Discussionsupporting
confidence: 92%
“… 25 Additionally, some radiologists may face difficulty in image interpretation via teleradiology due to the insufficient integration of patient history or previous examination, as well as the lack of communication with the referral clinicians. 22 The results showed that associate professors were more satisfied with the role of teleradiology during the COVID-19 pandemic than others, which may stem from the current practice of those who work in the academic field, as teleradiology systems allow for hybridized academic practice, in which academicians can have a part-time non-teaching clinical role via teleradiology in addition to their role as a teacher. 7 The potential selection bias (such as imbalance between clinical radiologists and academicians in the survey population) is attributed to the use of a non-probability convenient sampling technique, since the research question addressed by this technique is limited to the study population itself and thus lacks generalizability among clinical radiologists and academicians.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The company invested in an IT department that developed an individualized RIS and facilitated the integration of new customers. In a way, developments at TMC are similar to the development of noncommercial teleradiology networks worldwide [ 36 , 37 , 38 ]. Medical management and the IT department share the responsibility to decide about the introduction of a new AI product into a teleradiology service.…”
Section: Discussionmentioning
confidence: 99%
“…The ukb is a tertiary care, academic teaching hospital, and certified supra-regional trauma center with more than 730 beds, 17 operating theatres, a dual-use helicopter, and one of the busiest interdisciplinary stroke units in the capital of Germany. Given its mobile stroke unit and wide-ranging tele-neurology service, the ukb emerged as a premier national referral institution for acute neurological and neurosurgical cases [33,34]. All clinical investigators are board-certified and have renowned expertise in neurosurgery, neuroradiology, and endovascular interventions.…”
Section: Study Setting {9}mentioning
confidence: 99%